El Somontano: un viñedo en construcción - Cazenave-Piarrot, A. (Geographicalia, 2016)
The vineyard of Somontano in Aragon has expanded recently, after obtaining an AOC label in 1984. It stretches over about 3,000 ha, and its constantly rising production reached 100,667 hectolitres in 2002. It is actually a new vineyard set up in an old wine-producing area. This new wine-growing activity follows three main lines: a diversification of grape varieties, an oenological policy and, above all, a dynamic marketing. The business is dominated by three leading bodegas -Viñas de Vero, Pirineos, Enate- with a reciprocal shareholding, mainly owned by private bosses, even if some the shares are held by the Government of Aragon. The promotion of this vineyard had been based on the culture of Upper Aragon, vindicating an old wine-growing tradition and using the geographical situation as a distinctive referent, especially the mountain which serves as a background to the new wine-growing landscapes. This vineyard is also a way of asserting the dynamism of economy in Aragon, and, even more broadly, of the movida, the movement that has been associated with the take-off and social changes in Spain for the last two decades.